Can terminators be used as insulators into yeast synthetic gene circuits?. Issue 1 (December 2016) - Song, Wenjiang; Li, Jing; Liang, Qiang; Marchisio, Mario
Abstract Background In bacteria, transcription units can be insulated by placing a terminator in front of a promoter. In this way promoter leakage due to the read-through from an upstream gene or RNA polymerase unspecific binding to the DNA is, in principle, removed. Differently from bacterial terminators, yeastS. cerevisiae terminators contain a hexamer sequence, the efficiency element, that strongly resembles the eukaryotic TATA box i.e. the promoter sequence recognized and bound by RNA polymerase II. Results By placing different yeast terminators (natural and synthetic) in front of the CYC1 yeast constitutive promoter stripped of every upstream activating sequences and TATA boxes, we verified that the efficiency element is able to bind RNA polymerase II, hence working as a TATA box. Moreover, terminators put in front of strong and medium-strength constitutive yeast promoters cause a non-negligible decrease in the promoter transcriptional activity. Conclusions Our data suggests that RNA polymerase II molecules upon binding the insulator efficiency element interfere with protein expression by competing either with activator proteins at the promoter enhancers or other RNA polymerase II molecules targeting the TATA box. Hence, it seems preferable to avoid the insulation of non-weak promoters when building synthetic gene circuit in yeastS. cerevisiae .